2016
DOI: 10.1186/s13024-016-0115-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy targeting pyroglutamate-3 Aβ: prospects and challenges

Abstract: Immunization against amyloid-β (Aβ) peptides deposited in Alzheimer’s disease (AD) has shown considerable therapeutic effect in animal models however, the translation into human Alzheimer’s patients is challenging. In recent years, a number of promising Aβ immunotherapy trials failed to reach primary study endpoints. Aside from uncertainties in the selection of patients and the start and duration of treatment, these results also suggest that the mechanisms underlying AD are still not fully understood. Thorough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 82 publications
0
34
0
Order By: Relevance
“…57,64,[67][68][69][70] LY3002813, or N3pG, targets Aβ whose N-terminal two amino acids are removed and whose third amino acid is cyclized into pyroglutamate (pGlu-3 Aβ), making it more amyloidogenic and neurotoxic. 56,71,72 N3pG decreased brain amyloid and is being tested in a larger trial. 56,64 In trials of crenezumab, which also targets pyroglutamate Aβ, Aβ oligomers were reduced by a median of 43% (with intravenous delivery) or 48% (with subcutaneous delivery) in CSF, and the highest dose may have raised CSF Aβ and decreased brain amyloid while slowing decline, particularly in the milder AD patients.…”
Section: Vaccination For Admentioning
confidence: 99%
See 1 more Smart Citation
“…57,64,[67][68][69][70] LY3002813, or N3pG, targets Aβ whose N-terminal two amino acids are removed and whose third amino acid is cyclized into pyroglutamate (pGlu-3 Aβ), making it more amyloidogenic and neurotoxic. 56,71,72 N3pG decreased brain amyloid and is being tested in a larger trial. 56,64 In trials of crenezumab, which also targets pyroglutamate Aβ, Aβ oligomers were reduced by a median of 43% (with intravenous delivery) or 48% (with subcutaneous delivery) in CSF, and the highest dose may have raised CSF Aβ and decreased brain amyloid while slowing decline, particularly in the milder AD patients.…”
Section: Vaccination For Admentioning
confidence: 99%
“…Removing pGlu-3 Aβ may be more effective that targeting other forms of Aβ. 56,71,72 Several trials showed the strongest trends toward protection by passive immunotherapy in the mildest cases, suggesting that Aβ removal may help only in early stages of AD, perhaps even before any cognitive change but after some biomarkers have changed, such as CSF Aβ42 level, which falls a quarter century before dementia onset. 61,73,[77][78][79] Therefore, trials have been started in cognitively normal people who have mutations that will later cause early-onset AD (Alzheimer' 29,65,80,81 Several passive immunotherapy trials have targeted tau.…”
Section: Vaccination For Admentioning
confidence: 99%
“…For experimental studies, we used the Tg-F344-AD rat model that exhibits key hallmarks of human Alzheimer's disease such as Aβ and tau pathology, synaptic loss, and age-dependent cognitive impairment (29). Of major significance to our study, this rat model has significant and early accumulation of pE3-Aβ, which is present in human disease but generally lacking in mouse models (30). In order to distinguish effects of age, disease, and length of ligation, we microsurgically treated young and old TgF344-AD rats and used a generalized linear model to assess these independent variables.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, recent studies have proposed that immunization against less abundant but potentially more amyloidogenic and more neurotoxic isoforms of Aβ, such as AβpE3, could improve tolerability and efficacy in Aβ immunotherapy (29)(30)(31). These studies, however, are so far limited to passive immunization using antibodies previously screened in vitro for their specificity to AβpE3 and non-cross-reactivity to full-length Aβ.…”
Section: Introductionmentioning
confidence: 99%